Improving Student Learning Outcomes in Buying and Selling Material Through the Application of Role Playing Methods to Students of Madrasah Ibtidaiyah Ma'arif NU 1 Pancasan - Sugiarti, Wiwi; Gusriani, Wira; Wiwie; Winda; Winarti (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students' learning outcomes in the material of buying and selling through the application of the role-playing method in class VI MI Ma'arif NU 1 Pancasan, Ajibarang District, Banyumas Regency. The role-playing method was chosen because it can increase student involvement in the learning process, help them understand the concept of buying and selling contextually, and develop social and communication skills. This study uses a classroom action approach (CAR) which is implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data were collected through learning outcome tests, observations, and interviews with students and teachers. The results showed that the application of the role-playing method significantly improved students' understanding of the material of buying and selling. There was an increase in the average student score from the first cycle to the second cycle, as well as an increase in active participation in learning. Thus, the role-playing method has proven effective in improving student learning outcomes. This study recommends the use of this method as an alternative in learning the material of buying and selling, especially at the elementary school or madrasah ibtidaiyah level. Teachers are expected to be able to develop variations in its application to make it more interesting and in accordance with students' needs.